Exploring the Pathway towards Depression among Working Married Women – A Qualitative Study Done In Urban Area of Kancheepuram District, Tamil Nadu - Ramesh, Keerthana; R, Umadevi; VM, Anandhaeashwar; RJ, Charulatha; V, Nithya (National Journal of Community Medicine, 2022)
Introduction: Globally, around 264 million people suffer from depression according to World Health Organization (WHO). As per the National Mental Health Survey (NMHS), in the year 2015-2016, one in 20 people over the age of 18 years have ever had depression in India amounting to 45 million persons with depression in the year 2015. This study aimed to find out the self-perceived reasons of depression among married working women residing in an urban area of Kancheepuram district, Tamil Nadu. Methodology: This is a qualitative study done on married working urban women above 18 years of age visiting an UHTC of a private medical college at Anakaputhur. Patient Health Questionnaire (PHQ-9) was used to assess whether they have depression. Data was collected by in-depth interviews, and it was recorded and transcribed verbatim. Results: Based on the responses obtained from the participants the following themes and subthemes are formed like Workplace factors, Factors related to family, social factors and Mental Health seeking behaviour. Among the workplace factors job satisfaction, long working hours and relationship with peers were common reasons elicited. Conclusion: Most of these problems could be overcome only if the society changes their mentality about women and practice gender equality and social justice.